The development of indigenous public epigraphy in the Western Mediterranean: the ENCEOM database (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The aim of this article is to present the preliminary results of the ENCEOM database. Created as one of the main objectives of the Spanis research project "el nacimiento de las culturas epigráficas del Mediterráneo Occidental", the database looks for the compilation of public displayed inscriptions in indigenous languages and writings and its relationship with the romanization process.
Keywords: Romanization; Epigraphic Culture; Publicly Displayed Epigraphy; Epigraphic Databases